2012
DOI: 10.1159/000329484
|View full text |Cite
|
Sign up to set email alerts
|

Immune Outcomes of Paradoxical Sleep Deprivation on Cellular Distribution in Naive and Lipopolysaccharide-Stimulated Mice

Abstract: Background/Aims: Several lines of evidence indicate that sleep loss imposes significant consequences on the host defense system, including changes in cell number, activity and distribution. However, it is not clear whether cellular alterations after sleep deprivation are caused by redistribution to immune organs or by death of these cells or how the response to a nonspecific immune activator would be affected. Therefore, the aim of this study was to assess the leukocyte distribution after paradoxical sleep dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
5
11
1
Order By: Relevance
“…Pruritus, depression, and pain interfere with sleep duration and structure by increasing nocturnal awakenings and leading to sleep deprivation and fragmentation [17]. Lack of sleep itself has important effects on immunological integrity and nocturnal secretion of cytokines [18], [19], [20], [21], [22], [23], [24] and may be considered another risk factor for psoriasis. This bi-directional interaction between the central nervous system and the immune system has been focus of intense research in recent decades [25].…”
Section: Introductionmentioning
confidence: 99%
“…Pruritus, depression, and pain interfere with sleep duration and structure by increasing nocturnal awakenings and leading to sleep deprivation and fragmentation [17]. Lack of sleep itself has important effects on immunological integrity and nocturnal secretion of cytokines [18], [19], [20], [21], [22], [23], [24] and may be considered another risk factor for psoriasis. This bi-directional interaction between the central nervous system and the immune system has been focus of intense research in recent decades [25].…”
Section: Introductionmentioning
confidence: 99%
“…bees (Beyaert et al, 2012), songbirds (Jones et al, 2010), rodents (Zager et al, 2007;Zager et al, 2012)]. A growing body of experimental and epidemiological studies has demonstrated that sleep loss induces alterations in the immune system that predispose individuals towards disease (Faraut et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Even a single night of partial sleep loss can induce a rapid increase in nuclear-factor-kappa B activity, the transcription factor that promotes pro-inflammatory gene expression (Irwin et al, 2008;Irwin et al, 2010). Alternatively, during an infection or inflammatory challenge, such as bacterial lipopolysaccharide (LPS) exposure, sleep deprivation attenuates cellular immunity (Zager et al, 2012), alters sickness behavior (Zager et al, 2009) and suppresses pro-inflammatory mRNA expression in the periphery and brain (Weil et al, 2009). A common feature of sleep loss is activation of the hypothalamic-pituitaryadrenal axis (Meerlo et al, 2002), which leads to a moderate and transient elevation in circulating glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%
“…The literature indicates that SD modifies the profile of circulating leukocytes and the production of cytokines in human and animal models, with or without immunological challenge [31][32][33][34][35][36]. Moreover, it is also well described that stress hormones prevent the migration and activation of leukocytes [37].…”
Section: Discussionmentioning
confidence: 99%